Rola rachunkowości i audytu finansowego w zarządzaniu przedsiębiorstwem prowadzącym działalność w warunkach ryzyka - Sawicki, Kazimierz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The activity of an enterprise is connected with risk leading to bankruptcy of many entities. Aiming at minimizing negative effects of risk, the management searches for miscellaneous methods and tools and uses thorn. The paper presents in what way financial and management accounting as well as internal and external financial audit support managing large enterprises which operate under risk. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 395-404